Automatic parking sensor system / Muhammad Affiq Danial Amran & Mohamad Syukri Fadzil - Amran, Muhammad Affiq Danial; Fadzil, Mohamad Syukri (2015)
The Automatic Parking Sensor System using develop in this project is to determine the number of free space at car park using LDR sensor and microcontroller while the result will be display at Liquid Crystal Display (LCD). The ability of this project is to count accurately and automatically the number of free space at the parking in real time. The principle objective of this project was to provide the information of parking spaces either it is still available. This project is built base on the combination of hardware and software. The hardware part is use Arduino microcontroller to control whole system. The software part for the system has coded in C programming language. The LDR sensor will be able to detect vehicles that park and the counted number will be displayed on LCD. The output of this project is a complete device counter that can count the number of available vehicle at the parking on LCD and this paper will cover for the whole operation the system of Automatic Parking Sensor System.